2010
DOI: 10.1002/jbm.a.32696
|View full text |Cite
|
Sign up to set email alerts
|

Collagen type I hydrogel allows migration, proliferation, and osteogenic differentiation of rat bone marrow stromal cells

Abstract: Hydrogels are potentially useful for many purposes in regenerative medicine including drug and growth factor delivery, as single scaffold for bone repair or as a filler of pores of another biomaterial in which host mesenchymal progenitor cells can migrate in and differentiate into matrix-producing osteoblasts. Collagen type I is of special interest as it is a very important and abundant natural matrix component. The purpose of this study was to investigate whether rat bone marrow stromal cells (rBMSCs) are abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 62 publications
1
76
0
3
Order By: Relevance
“…At earlier time points, at 2, 4 or 6 h after seeding, the levels of osteoblast gene expression were similar in cells growing in 2D and 3D collagen cultures (data not shown). In a number of previous studies, 3,8,14,15 collagen gels were formed first and osteoblasts were seeded on top of the gels, allowing for the analysis of cell migration into the gels. Interestingly, while osteoblasts migrated into the gels and formed a 3D cell network, fibroblasts seeded on top of the gels migrated through them and formed a monolayer on the plastic underneath.…”
Section: Enhanced Osteoblastogenesis In 3d Gelsmentioning
confidence: 99%
See 3 more Smart Citations
“…At earlier time points, at 2, 4 or 6 h after seeding, the levels of osteoblast gene expression were similar in cells growing in 2D and 3D collagen cultures (data not shown). In a number of previous studies, 3,8,14,15 collagen gels were formed first and osteoblasts were seeded on top of the gels, allowing for the analysis of cell migration into the gels. Interestingly, while osteoblasts migrated into the gels and formed a 3D cell network, fibroblasts seeded on top of the gels migrated through them and formed a monolayer on the plastic underneath.…”
Section: Enhanced Osteoblastogenesis In 3d Gelsmentioning
confidence: 99%
“…It has been shown that culturing cells in 3D collagen gels affects cell shape, cell-cell interactions and response to soluble factors. 1,3 Collagen gels are also being considered in regenerative medicine of the musculoskeletal system as potential biomimetic bone replacement materials for use in cases of bone loss by trauma or disease. 4 Collagen I provides a tissue-derived natural polymer; it is biocompatible and biodegradable and its mechanical and biological properties can be controlled and varied as required.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both proteins serve as a scaffold for tissue regeneration and can promote the migration and ingrowth of cells. Fibrin and collagen are an ideal biomaterial for hydrogel scaffolds, because of their distinguished biocompatibility and cell adhesion capability [9,10].…”
Section: Introductionmentioning
confidence: 99%